Kiribati : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2011)
This report presents data provided by the authorities during 2005-09, which include Kiribati's contributions to GDP growth and gross national product. It provides a summary of central government's operations, revenue 2005-09, central government expenditure (functional and economic classifications), salary structure 2004-08, and budgetary subsidies to public enterprises. Details of assets and the liabilities of the Development Bank of Kiribati, provident funds, ANZ bank's balance sheets and interest rates, and composition of exports and imports are also mentioned. It shows services and income, external grants, and external assets and liabilities as well.